Improving the Ability to Appreciate Short Stories through a Student-Centered Learning Approach for Class X Students of SMK Negeri 1 Touluaan - Malinggas, Fientje; Liando, Mayske; Polii, Intama J.; Rotty, Viktory Nicodemus Joufree (AIBPM Publisher, 2020)
The purpose of this study is to improve the ability to appreciate short stories through Student Centered Learning Approaches Class X Students of SMK Negeri 1 Touluaan. This research was conducted at SMK Negeri 1 Touluaan, Academic Year 2019/2020 Academic Year of 48 students. The method used in this research is classroom action research. The first round is 47% in the underprivileged category, the second half 62% is still in the underprivileged category, and 80% of the third round is in the underprivileged category. Students' appreciation for the ability to determine the intrinsic elements of a short story can increase if they exchange ideas and discuss together and present the results of each group's discussion to be responded to by other groups. This will make the Student-Centered Learning (SCL) approach can improve students' ability to appreciate the intrinsic element of the Indonesian short story learning. Particularly, in short story learning, teachers must be able to create a pleasant learning atmosphere by implementing effective learning.